Segregated Miscegenation : On the Treatment of Racial Hybridity in the North American and Latin American Literary Traditions. - Hiraldo, Carlos, 1971- (Literary criticism and cultural theory., 2014)
First Published in 2003. Routledge is an imprint of Taylor & Francis, an informa company.